Development of Avocado and Lemon Oil Emulgels Based on Natural Products: Phycocyanin and Pectin - Patricia Tello; Nuria Calero; Jenifer Santos; Luis A. Trujillo-Cayado (Pharmaceutics, 2023)
Phycocyanin (PC), a natural product obtained from algae, is attracting attention due to its health benefits, such as its antioxidant and anti-inflammatory properties. This work studies the use of PC as the main stabilizer in avocado and lemon oil emulgels, a format for drug delivery. The influence of PC concentration on droplet size distribution, rheological properties, and physical stability is studied using a laser diffraction technique, rheological measurements, and multiple light scattering. The 5 wt.% PC emulsions show the lowest droplet size and, consequently, the best stability against creaming and droplet growth. Emulsions formulated with PC as the only stabilizer show a slight pseudoplastic character with an apparent viscosity below 10 mPa·s at 2 Pa. This indicates that these emulsions undergo creaming with aging time. In order to reduce creaming, pectin is incorporated into the 5 wt.% PC emulsion at different concentrations. Interestingly, yield stress and an incipient gel character are observed due to the presence of pectin. This is why the creaming mechanism is reduced. In conclusion, PC forms a layer that protects the interface against coalescence and Ostwald ripening. And, pectin is incorporated to reduce creaming. This research has the potential to make valuable contributions to diverse fields, such as health, medicine, and encapsulation technology.